Electrochemical kinetics as a function of transition metal dichalcogenide thickness. (10th October 2021) - Brunet Cabré, Marc; Paiva, Aislan Esmeraldo; Velický, Matěj; Colavita, Paula E.; McKelvey, Kim
Abstract: Two-dimensional transition metal dichalcogenides are used as electroactive materials for electrochemical and electrocatalytic applications. However, it remains unclear how transition metal dichalcogenide thickness influences the electrochemical response measured at its surface. We use scanning electrochemical cell microscopy to assess the electrochemical response of different thicknesses of bottom-contacted MoS2, MoSe2, WS2, and WSe2 towards the simple outer-sphere redox couple [Ru(NH3 )6 ] 3+/2+ with submicron spatial resolution. A detailed analysis, coupling mass transport and electrochemical kinetics, reveals that the electrochemical response can be described using an electron tunneling barrier, which scales with the band gap of the two-dimensional transition metal dichalcogenide. Our results suggest that interpretation of the electrochemical and electrocatalytic responses on transition metal dichalcogenide-covered electrodes should account for the through-layer electron transport kinetics. Graphical abstract: Image, graphical abstract